Examining homicides and suicides cross‐nationally: Economic factors, guns and video games. (30th March 2021) - Ferguson, Christopher J.; Smith, Sven
Abstract : Understanding why different nations have different homicide and suicide rates has been of interest to scholars, policy makers and the general public for years. Multiple theories have been offered, related to the economy, presence of guns and even exposure to violence in video games. In the current study, several factors were considered in combination across a sample of 92 countries. These included income inequality (Gini index), Human Capital Index (education and employment), per capita gun ownership and per capita expenditure on video games. Results suggest that economic factors primarily were related to homicide and suicide cross‐nationally. Video game consumption was not a major indicative factor (other than a small negative relationship with homicides). More surprisingly, per capita gun ownership was not an indicator factor cross‐nationally. The results suggest that a focus on economic factors and income inequality are most likely to bear fruit regarding reduction of violence and suicide.